O vocabulário geométrico em livros didáticos dos anos iniciais do ensino fundamental - Coêlho, Larissa Ferreira (2017)
The present research had as objective to investigate the geometric vocabulary addressed in the activities of two collections of didactic books of the initial years of Elementary School. Considering results of investigations that pointed out the lack of vocabulary on the part of the students and teachers, as a factor of interference in the resolution of problems and in the construction of mathematical definitions, we decided to analyze the didactic book since usual terms of the Portuguese language are used to determine contents, objects and definitions, omitting the necessary mathematical language in the presentation of Geometry from the beginning to the end of the initial years. In this way, our study tried to answer the following question: "The activities proposed in didactic books of the initial years introduce the own vocabulary for the content of Geometry?" In order to obtain the answer, we perform an analysis based on criteria derived from the fundamentals of our preliminary studies and our problematic, directed by the Langlois study (2015), Wittgenstein's language games (2014) and current official documents of the Ministry of Education of Brazil. After analyzing the collections, we concluded that there are many weaknesses in the activities presented for the work with Geometry; we detected, besides the shortage of specific vocabulary in Mathematics, a wrong treatment with the solid geometric content and an overlap of the mother language